Museum DoorDacht : Patrick Vanden Eynde / John Baldessari / Neal Tait / Kristof Van Gestel / Marcel Van Eeden / Eugène Laermans / Edgard Tytgat / Marthe Wéry / Joëlle Tuerlinckx / Matthieu Ronsse. - Declercq, Joost; Museum Dhondt-Dhaenens, Deurle; Lambrecht, Luk; Cesteleyn, Ann; Bracewell, Michael; Kremer, Mark; Meskens, Ann; Eeckhout, Tanguy (Deurle : Museum Dhondt-Dhaenens, 2007)
Vanden Eynde, Patrick ; Baldessari, John ; Tait, Neal ; Van Gestel, Kristof ; Van Eeden, Marcel ; Laermans, Eugène ; Tytgat, Edgard ; Wéry, Marthe ; Tuerlinckx, Joëlle ; Ronsse, Matthieu
Tijdschrift over het MDD, o.a. over enkele projecten en tentoonstellingen het Museum Dhondt-Dhaenens, Deurle, in 2006 en 2007.
kunstcatalogus